Pengaruh Pemberian Aromaterapi Lemon dan Minuman Jahe Terhadap Pengurangan Emesis Gravidarum pada Ibu Hamil Trimester I - Dian Laila Novianita; Inda Corniawati; Frana Andrianur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Emesis gravidarum, or excessive nausea and vomiting during early pregnancy, is a common issue frequently experienced by pregnant women. Most cases of pregnancy-related nausea and vomiting can be managed through outpatient care and the use of sedatives and anti-emetics. However, the treatment of hyperemesis gravidarum, a more severe form of pregnancy-related nausea and vomiting, can be approached both pharmacologically and non-pharmacologically. One non-pharmacological approach involves the use of aromatherapy with lemon essential oil and the consumption of ginger-infused beverages. This study aims to analyze the effects of lemon aromatherapy and ginger beverage consumption on reducing emesis gravidarum symptoms in first-trimester pregnant women at the Kaubun Health Center. The research employs a Pretest-Posttest without Control Group design, with a sample of 30 first-trimester pregnant respondents. Statistical analysis using the Wilcoxon test reveals a significant difference in the reduction of emesis gravidarum symptoms between the group receiving lemon aromatherapy and the group consuming ginger beverages, with a p-value of 0.001. Based on these findings, it can be concluded that the administration of lemon aromatherapy and ginger beverage consumption has a positive impact on reducing emesis gravidarum symptoms in first-trimester pregnant women. This non-pharmacological approach can be an effective alternative for managing emesis gravidarum during early pregnancy.